The potential of fungi isolated from palm oil mill effluent (POME) for mycoremediation of water contaminated with pome waste - Zakaria, Zakaria; Ilmi, Miftahul; Kasiamdari, Rina Sri (Brawijaya University, 2026)
POME (Palm Oil Mill Effluent) is a liquid waste from fresh fruit bunch oil extraction that can damage the environment if the content of the waste is not processed correctly. This study aimed to determine fungi species that can potentially be POME waste remediation agents. Several stages carried out in this study included the isolation of fungi from POME waste, screening potential fungal isolates based on qualitative amylase, lipase, cellulase, and protease enzyme tests, and analysis of biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), oil and fat, and pH of POME waste liquid. There were 100 fungal isolates from POME waste disposal: 25 produced cellulase, 25 produced amylase, 25 produced protease, and 23 were capable of producing lipase. Based on the morphological characterization and confirmation by the molecular identification, the selected potential fungal isolate T3(16) was identified as Eutypella sp. The spectrophotometer test for optimal POME waste degradation showed that the degradation percentage by Eutypella sp. isolate T3(16) was 77.82% at a waste concentration of 25% with an incubation time of 168 hours. SEM results from Eutypella sp. T3(16) showed that fungal cells were damaged, with thickening observed as a defense mechanism against environmental stressors and the POME waste biosorbent process. The results of the physicochemical test showed a reduction of 95.10% in BOD, 95.15% in COD, 99.94% in Oil and Fat, and 94.77% in TSS, while the pH increased from 5.0 to 7.2.